PENGAMALAN KUALITAS SIFAT PRIBADI KEPIMPINAN TRADISIONAL BAGI KEPALA DAERAH DALAM MEWUJUDKAN KESEJAHTERAAN RAKYAT - Samah, Abu; Bin Embi, Muhamad Ali (Humanus, 2015)
The purpose of this study is to comprehend personal characters in Indonesia’s traditional leadership and its correlation with the regional leadership. This study uses descriptive analyses method by library research. The result shows that the regional leaders have low quality of personal characters that may lead to the failure to fulfill community’s welfare. Therefore the regional leaders have to implement the personal characters of Indonesia’s traditional leaders along with the Regional Governance Law No. 12 2008, revised by Law No. 23 2014 in order to increase the people’s income, improve education, guarantee health facilities and housing, as well as reduce poverty and unemployment rate in the region.Keywords: regional leaders, Kampar regency, community welfare, personal characters